Analisis Kualitas Sistem Informasi Layanan pada PT. Inti Jasa Kreatif Menggunakan Metode Webqual 4.0 - Putri, Nuryani Mawar; Achyani, Yuni Eka (STMIK Palangkaraya, 2024)
PT Inti Jasa Kreatif is an Event Organizer company that relies heavily on the quality of information systems to maintain smooth operations, efficiency, and client satisfaction. This company uses websites to convey business information. To improve the quality of design and user interaction, PT Inti Jasa Kreatif uses the WebQual 4.0 method in analyzing website quality. This study will analyze the quality of the service information system www.intijasakreatif.co.id with a focus on the aspects of usability, informativeness, and trustworthiness, measuring client needs and satisfaction with services using the Webqual 4.0 method. The Webqual 4.0 method is a method developed to measure the quality of web-based services with the data used being the respondents of the questionnaire that has been distributed. The data collection method uses primary data in the form of questionnaires distributed to 102 respondents. Based on data processing, it can be seen that in the validity test of variable X1 (Usability Quality) the results show that variable X1 correlates with the potential quality of website usability that respondents find it easy to use the website application. From the results above, the author concludes that variable X1 has more influence than variables X2 and X3 on user satisfaction.